Gengangerhændelser - Raahauge, Kirsten Marie (Tidsskrift for kulturforskning, 2016)
Since 2007 I have interviewed people in Denmark about their extraordinary experiences in connection with my project Haunted Houses. The interviewees give accounts of unex-plainable, aimless experiences that they somewhat hesitant call haunting; often they also state that they are not sure about what the word actually means, and whether it covers the experience. This article takes its point of departure in the interviewees’ attempts to connect their extraordinary experiences with their everyday life and their ordinary models for explanation, and it deals with the difficulties it produces to investigate this field of exceptions. Typically, the experiences are small, insignificant occurrences with extraordi-nary overtones, such as sounds in rooms that seem to be empty, paintings that fall of their hooks, or iPhones that makes calls without a sender. For many of my interviewees such experiences fall into cracks and fissures of common sense rationalities; by resisting common sense they open up for a wilder interpretation of the world. Maybe it was not a ghost, you saw or heard, but what was it then? And, if we call it a ghost, what does it mean? Some wait for the next extraordinary occurrence that might confirm that what they heard or saw was not a hallucination, but in fact it happened, although it seemed unreal. These extraordinary occurrences challenge our rational explanations, albeit only on a small scale, and they point to the limits of our reason, and of what we are capable of understanding; sometimes they even broaden these limits.